PHYSIOLOGICAL CARDIO-RESPIRATORY CHANGES OF AMARNATH YATRIES AT DIFFERENT HEIGHTS OF YATRA: AN OBSERVATIONAL STUDY. - Dr. Rajendra Kumar (Student's Journal of Health Research, 2023)
Introduction: More than 3.5 lacs Amarnath Yatries ascend each year to holy Amarnath Cave situated about 3888 meters from the sea level. During ascent for Yatra in the mountains experiences multiple environmental stressors, but the stress unique to high altitudes is the oxygen-deficient atmosphere. This work focused on Physiological cardio-respiratory changes of Amarnath Yatries at different heights of Yatra. Methods: An observational study on Blood Pressure, Oxygen Saturation, Respiratory rate, and Pulse rate was conducted among 75 Amarnath Yatries at different heights during Amarnath Yatra from month of June and July in three years 2012, 2013, and 2014 respectively, and the researcher himself accompanied those groups during all 3 years after receiving ethical approval from Institutional Review Committee RIMS Ranchi and informed consent from Yatries. Results: Oxygen saturation (%) was 97.7±1.8 at Ranchi (control value), this value on exposure to high altitude, at Amarnath Cave (12500 feet) decreased to 75.2±4.3 %. Respiratory Rate (RR) was 15.5±1.8 per minute at Ranchi (control value), this value on exposure to high altitude, at Amarnath Cave (12500 feet) increased to 31.3±2.9 per minute. Pulse Rate (PR) was 87.6±11.9 per minute at Ranchi (control value), this value on exposure to high altitude, at Amarnath Cave (12500 feet) increased to 121.2±10.3 per minute. Conclusion: Blood Pressure, Respiratory rate, and Pulse rate of Amarnath Yatries significantly increase while Oxygen Saturation decreases at Holy Amarnath Cave.